The impact of government intervention on innovation efficiency of green technology—a threshold effect analysis based on environmental taxation and government subsidies - Li, Liqin; Rao, Minye (Frontiers in Energy Research, 2023)
Research and promotion of green technology can improve energy efficiency and help to optimize energy structure, which are key considerations in achieving the “dual carbon” goals of carbon peaking and carbon neutrality. Owing to the “dual externality” arising from green technology innovation (GTI), government policies have an important impact on this area. Environmental taxes and government subsidies are important means for governments to improve GTI and optimize energy utilization, with different environmental taxes and subsidies having different impacts. This study evaluates the impact of environmental taxes and government subsidies in China from 2009 to 2019, and assesses how these policies interacted with each other to determine China’s efficiency in GTI over this period. The study’s findings based on analysis of 30 provinces and cities in China indicate that environmental taxes have a threshold effect on the development of green technologies, and that the current level of taxation is insufficient to encourage optimized development in this area. Government subsidies can also help to reduce the negative effects arising from the current environmental tax burden. To optimize government policy implementation in this area, improve the level of GTI, and improve energy use efficiency, this study proposes countermeasures based on differentiated policies, including gradually increasing the rate and scope of environmental taxation, and strengthening the supervision of government subsidies.